Graphite from biomass: A review on synthetic feasibility - Cherakkara, Aswathi; Zafar, Saima; Izan Izwan, Misnon; Yang, Chun-Chen; Jose, Rajan (Elsevier, 2025)
Graphite forms the basis of a multibillion-dollar industry; obtained either by mining or by synthesis from petrochemicals with significant energy and materials footprints. Biomass is a carbon-negative and renewable precursor; therefore, obtaining graphite from bioresources is a step forward in the pursuit of sustainability. Herein, we review the advances in their synthesis following conventional (direct pyrolysis, activation, catalytic graphitization, and simultaneous activation-graphitization) and advanced methods (flash joule heating, microwave synthesis, and ultrasonic-assisted synthesis), highlighting their advantages and limitations. Carefully examining the process parameters, mechanisms, and environmental impacts of existing synthetic methods of graphite, we outline the progress and gaps. This review underscores the need for further research to refine the existing techniques, optimize process parameters, and develop scalable, environmentally friendly graphite production processes. Future research to be focused on novel highly abundant biomass feedstocks with high carbon content and easy processability. A comprehensive assessment of the environmental impact of the synthesis processes is crucial, including waste generation and disposal, to ensure the benefits of biomass-derived graphite do not come with unintended ecological consequences. Optimisation of carbonization and graphitisation techniques are essential to improve efficiency, reduce energy consumption, and enhance the quality of the resulting graphite materials.